IgM lambda cytoplasmic crystals in three cases of immunocytoma: a clinical, cytochemical, and ultrastructural study. Issue 3 (March 1978) - Feremans, W W; Neve, P; Caudron, M
Abstract : Endoplasmic reticulum-associated crystals were seen in 1-10% of the bone-marrow lymphocytes and in the lymphocytes of the peripheral blood in three cases of immunocytoma. Their crystalline nature and their location in the cisternae of the rough endoplasmic reticulum was proved by ultrastructural study. IgM lambda in the crystals was demonstrated by fluorescent and peroxidase-labelled antibody methods. The crystals did not stain with the PAS reaction, suggesting that the immunoglobulin was not bound to a carbohydrate group. A defect in glucosyltransferase activity with failure to modify the immunoglobulins could explain the absence of the PAS reaction and the accumulation of immunoglobulin in crystalline before reaching the Golgi region.